Editorial: Fruit and seed evolution in angiosperms - Sukhorukov, Alexander P.; Sousa-Baena, Mariane S.; Romanov, Mikhail S.; Wang, Xin (Frontiers in plant science)
The diversity of fruits and seeds is enormous all over the world, and they play a crucial role in all aspects of biology, including human life. Despite the long history of carpological research, many characteristics of fruit and seed structure and evolution, as well as dispersal mechanisms, seed germination, and the ecological parameters of fruit and seed traits, have been lacking attention so far. Recently developed comparative methods based on molecular phylogeny and other new technologies provide an excellent opportunity for tracing the evolution of fruits and seeds in various plant groups.